Does Farmland Scale Management Promote Rural Collective Action? An Empirical Study of Canal Irrigation Systems in China - Liangzhen Zang (MDPI AG, 2021)
Farmland scale management represents an inevitable trend toward global modern agriculture. In the new development context, the key to solving the tough problem of the insufficient supply of rural public goods is to effectively improve the enthusiasm of farming households to participate in rural collective action in countries with a small arable area per capita, such as India, China and countries in Eastern Europe. This paper adopts the Institutional Analysis and Development (IAD) framework in the context of a land system with Chinese characteristics, and uses sample data of 3663 rural households in 17 provinces to study the impact of farmland scale and various relevant systems on farming households’ participation in rural collective action. We found that the advantages of collective action, such as reduced production costs, enhanced risk resistance and improved production efficiency, can offset the disadvantages incurred by free-riding behavior, and the expansion of farmland scale can significantly facilitate rural collective action. Additionally, as the farmland scale expands, stable farmland tenure and reasonable farmland tenure transfer can help to optimize the allocation of arable land resources, increase investment, and reduce free-riding behavior, thus effectively stimulating farming households to actively participate in collective action. However, since socialized agricultural services lead to the separation of the suppliers and the users of rural public goods, the expansion of farmland scale shows a negative effect. Therefore, in the context of the continuous migration of the rural population to cities, a stable farmland tenure adjustment mechanism should be established, while the balance between farmland tenure transfer and socialized agricultural services, in pushing forward rural collective action, should be emphasized, so as to ensure the effective supply of rural public goods in propelling farmland scale management. Especially in promoting the development of socialized agricultural services, more attention should be paid to specifying the responsibilities and obligations of the main provider of commercialized services in the supply of rural public goods.